INCIDENCE OF MENTAL PROBLEMS OF CHILDREN IN PRIMARIES SCHOOLS - Pochybová, Martina; Ondrejka, Igor; Tokoš, Zuzana (Profese Online, 2009)
Our researych was focused on the incidence of mental problems disorder in children in primaries schools. The aim of the work was to identify range of occurrence of psychological problems of children in the primaries schools of 7to 15. The spectrum of the occurrence of psychological problems was assessed by using Conners Parent Rating Scale (CPRS) (Conners, 1972). It was detected numerous existence of psychological problems in children at primaries schools from malfunction with food intake, anxiety disorders, hyperactivity and problems with learning difficulties.
Keywords: psychiatric problems; children; nursing; primary schools; CPRS